Aerodynamic loading acting on the stator vane in the variable nozzle turbine flow - Žatko M. (Applied and Computational Mechanics, 2015)
The purpose of this paper is to evaluate an aerodynamic loading acting on the stator vanes of the turbocharger using variable nozzle turbine (VNT). Computational fluid dynamic (CFD) is applied using commercial software ANSYS CFX. A full turbine stage CFD model is used to investigate the aerodynamic loading in several operating points for different stator vane positions. Results are compared with the measurement on the Gas Stand testing rig. This device burns natural gas and produces a stable flow at very high temperatures. This excludes the impact of the engine control management, the engine vibrations, and the flow pulsations on measured values. A comparison of measured and simulated vane aerodynamic loading provides a very good correlation. These encouraging results show a high potential of CFD methods for further development and optimization of VNT mechanism.